Mineral nutrition of campos rupestres plant species on contrasting nutrient‐impoverished soil types - Oliveira, Rafael S; Galvão, Hugo C; Campos, Mariana C. R; Eller, Cleiton B; Pearse, Stuart J; Lambers, Hans (The New phytologist, 2015)
In Brazil, the campos rupestres occur over the Brazilian shield, and are characterized by acidic nutrient‐impoverished soils, which are particularly low in phosphorus (P). Despite recognition of the campos rupestres as a global biodiversity hotspot, little is known about the diversity of P‐acquisition strategies and other aspects of plant mineral nutrition in this region. To explore nutrient‐acquisition strategies and assess aspects of plant P nutrition, we measured leaf P and nitrogen (N) concentrations, characterized root morphology and determined the percentage arbuscular mycorrhizal (AM) colonization of 50 dominant species in six communities, representing a gradient of soil P availability. Leaf manganese (Mn) concentration was measured as a proxy for carboxylate‐releasing strategies. Communities on the most P‐impoverished soils had the highest proportion of nonmycorrhizal (NM) species, the lowest percentage of mycorrhizal colonization, and the greatest diversity of root specializations. The large spectrum of leaf P concentration and variation in root morphologies show high functional diversity for nutritional strategies. Higher leaf Mn concentrations were observed in NM compared with AM species, indicating that carboxylate‐releasing P‐mobilizing strategies are likely to be present in NM species. The soils of the campos rupestres are similar to the most P‐impoverished soils in the world. The prevalence of NM strategies indicates a strong global functional convergence in plant mineral nutrition strategies among severely P‐impoverished ecosystems.